PENINGKATAN PROFESIONALISME GURU POLEWALI MANDAR MELALUI PELATIHAN TINDAKAN KELAS (PTK) - Nur Amaliah; Syamsiara Nur; Firman Firman; Sari Rahayu Rahman; Sainab Sainab (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2023)
The improvement of the quality of education is important to the advancement of a nation and is the responsibility of all parties, including goverment, the private sector, individuals and others. In learning activities, a teacher will certainly be confronted with various problems, both students, subject matter and learning methods. One of the ways that professional educators can make to enhance the quality of learning is action research in the classroom. Presently KGP Polewali Mandar has never organised any training events for other teachers, so this community needs partners who can be brought together to train teachers in Polewali Mandar in order to enhance the professionalism of teachers in district. The PKM team worked with the KGP to provide on teacher training and mentorship. It took place from April to June 2022. This event was attended by 103 teachers in Polewali Mandar vi online. The title of the workshop activity on